The Interplay of Socio-Cultural, Religiosity and Law Perspectives Toward Gender Role Distribution in Co-Preneurship Business Practice - Rahman, Hafiz; Oktavia, Sri; Nurul Qulbi, Atikahasri Ursyifa; Wulandari, Rifa Cantika; Shetye, Niyanta (Udayana Journal of Law and Culture, 2025)
This study highlights the complex interplay of social, cultural, and religious factors in shaping gender roles within co-preneurial businesses in Indonesia. Using an empirical qualitative approach, the research incorporates in-depth interviews with seven co-preneurial couples from diverse cultural backgrounds i.e., Javanese, Minangkabau, and Mandarese ethnicities in Indonesia. The findings reveal that co-preneurial couples often challenge traditional gender stereotypes by establishing equitable roles based on individual capacities rather than societal norms. This flexibility is underpinned by mutual trust, effective communication, and respect, crucial for entrepreneurial endeavour. Cultural analysis shows that Javanese and Mandarese cultures, while patriarchal, allow for adaptable role distributions. Meanwhile, Minangkabau culture, which is matrilineal, is more gender-balanced. From a religious perspective, all participants view Islam as advocating for collaborative efforts between male and female in business and promoting balanced gender roles. Despite traditional biases favouring male dominance in work and industry, current trends indicate increasing female involvement in business activities, challenging long-standing stereotypes. The study identifies potential disadvantages, including conflicts arising from the overlap between personal and professional roles and underlying cultural and social biases influencing role dynamics. The study implies that advocating more intensive gender equality, establishing clearer professional boundaries, developing supportive policies and legal frameworks to foster an equitable co-preneurial environment are still needed, which should emphasize the importance of mutual respect, trust, and flexibility in creating balanced and productive business partnerships, contributing valuable insights into the intersection of law, culture, and entrepreneurship.